Commonalities and distinctions of pediatric patient and family engagement in clinical care, education, and research contexts: Protocol for a scoping review - Brooke Allemang; Francine Buchanan; Pranshu Maini; Dalya Kablawi; Lin Li; Linda Nguyen; Kimberly Courtney; Jessie Cunningham; Carla P. Southward; Kristin Cleverley; Sarah Munce; Alene Toulany (PLoS ONE, 2025)
Background Pediatric patient and family engagement is an active and collaborative process, that involves children, adolescents, and family members with lived experience contributing to the design, implementation, and evaluation of healthcare services. Prior studies have highlighted the patient engagement methods and impact in clinical care, education, and research. However, gaps remain in understanding the commonalities and distinctions of engagement approaches, patient/family partner roles, and outcomes in clinical care, education, and research contexts. Further, research examining the nuances of pediatric patient and family engagement within healthcare delivery, education, and research in pediatric institutions is needed to streamline efforts. Objective This scoping review will identify the commonalities of and distinctions between pediatric patient and family engagement in clinical care, education, and research contexts in pediatric healthcare institutions. Methods A scoping review, conducted in collaboration with a team of adolescent, young adult, and family partners, will allow us to systematically map out key concepts, evidence, and knowledge gaps regarding pediatric patient and family engagement in clinical care, education, and research. We will follow the Joanna Briggs Institute framework in the design and conduct of the review and guidance on engaging knowledge users within scoping reviews. The protocol for this scoping review has been registered with the Open Science Framework database (https://osf.io/63qx5). Results This study will describe the engagement types, approaches, and outcomes of pediatric patient and family engagement employed within clinical care, education, and research settings, highlighting commonalities and distinctions across contexts. In doing so, it will identify potential opportunities for collaboration and resource-sharing based on the context of engagement and provide needed clarity on streamlining pediatric patient and family engagement approaches within pediatric institutional settings. Conclusions It is anticipated that the results will produce preliminary evidence of relevance to pediatric institutions seeking to consolidate engagement practices across clinical care, education, and research domains.